2001
DOI: 10.1016/s0141-0296(00)00075-4
|View full text |Cite
|
Sign up to set email alerts
|

A repairability index for reinforced concrete members based on fracture mechanics

Abstract: This paper proposes a repairability index for damage assessment in reinforced concrete structural members. The procedure discussed in this paper differs from the standard methods in two aspects: the structural and damage analyses are coupled and it is based on the concepts of fracture and continuum damage mechanics. The relationship between the repairability index and the wellknown Park and Ang index is shown in some particular cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
0
7
0
3
Order By: Relevance
“…As soon as the reinforcement initiates its yielding process the damage growth turns less accel-erated. At the instant that the structure reaches the maximum value of load resistance measured experimentally (see [22]), the damage on hinge '2' presents itself with intensity about 0.6, which is considered excessive to reinforced concrete structures, [23]. From this point on, the structure continues to deform in a process of controlled displacement.…”
Section: Prestressed and Precast Concrete Segmental Liningmentioning
confidence: 99%
See 2 more Smart Citations
“…As soon as the reinforcement initiates its yielding process the damage growth turns less accel-erated. At the instant that the structure reaches the maximum value of load resistance measured experimentally (see [22]), the damage on hinge '2' presents itself with intensity about 0.6, which is considered excessive to reinforced concrete structures, [23]. From this point on, the structure continues to deform in a process of controlled displacement.…”
Section: Prestressed and Precast Concrete Segmental Liningmentioning
confidence: 99%
“…Notice that the constitutive model, represented by the set of equa-tions (23,26,28) is also nonlinear. Therefore, it is necessary the use of Newton's method combined with a predictor and corrector strategy in local character.…”
Section: Numerical Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, values of damage less than 0.2 can be described as minor, repairable damages are in the range [0.2, 0.45] and values over 0.6 corresponds to progressive collapse. Theoretical and experimental justification for these values can be found in [14].…”
Section: Numerical Examplesmentioning
confidence: 99%
“…The other analysis based on theory of fracture mechanics (Enrique, 2001 ) suggested that the damage state could be represented by the strain energy by calculating the lost energy and the crack resistance of the plastic hinge. A damage function was also suggested by accumulating the plastic deformation (Stephens & Yao, 1987 ), where the plastic deformation is similar to the maximum deflection as in previous damage index.…”
Section: Introductionmentioning
confidence: 99%